The Use of English Songs to Teach Pronunciation to the Tenth Graders of SMA Negeri 4 Surabaya (RETAIN, 2016)
The Use of English Songs to Teach Pronunciation to the Tenth Graders of SMA Negeri 4 Surabaya Indah Kurnia Nurpratiwi English Education, Language and Art Faculty, State University Surabaya indahnurpratiwi@mhs.unesa.ac.id Fauris Zuhri, S.Pd. M,Pd English Education Department, Faculty of Language and Art, State University of Surabaya zuhrifauris@gmail.com Abstrak Pronunciation adalah salah satu bagian yang sulit dalam belajar bahasa Inggris. Hal ini didukung oleh fakta bahwa beberapa siswa mengalami kesulitan dalam pronunciation karena mereka kurang termotivasi untuk berbicara bahasa Inggris. Sulit bagi siswa Indonesia untuk mengucapkan kata bahasa Inggris dengan benar. Hal ini karena perbedaan antara bahasa pertama mereka dan bahasa target. Mahasiswa Indonesia khususnya siswa di SMA masih kesulitan dalam mengucapkan kata dengan benar karena mereka cenderung menggunakan bahasa utama mereka. Akibatnya, peserta didik tidak melafalkan kata-kata dengan jelas. Kebanyakan guru tidak memperhatikan pentingnya pronunciation. Menurut Harmer (2001: 183), guru merasa bahwa mereka sudah melakukan banyak hal dalam mengajar pronunciation. Guru tidak hanya harus menciptakan suasana yang baik selama mengajar kegiatan pembelajaran, tetapi juga menciptakan teknik mengajar yang menarik yang menyenangkan. Fauziati (2002) mengatakan bahwa lagu adalah media yang direkomendasikan untuk membuat siswa lebih antusias, memperhatikan subjek, dan meningkatkan minat siswa dalam materi dan itu bisa berpengaruh pada peningkatan pronunciation mereka. Penelitian ini merupakan penelitian deskriptif kualitatif. Instrumen yang digunakan untuk mendapatkan data dari penelitian ini adalah observasi checklis dan wawancara. Deskripsi checklist pengamatan meliputi: (1) Penggunaan lagu bahasa Inggris untuk mengajar pronunciation di kelas X SMA Negeri 4 Surabaya dan (2) Hasil pronunciation para siswa selama penggunaan lagu bahasa Inggris dalam mengajar pronunciation. Subyek penelitian ini adalah siswa kelas X-MIPA7 dan guru bahasa Inggris dari SMA Negeri 4 Surabaya. Hasil penelitian ini menunjukkan bahwa guru menggunakan lagu bahasa Inggris untuk mengajar pronunciation telah berjalan dengan baik. Hal ini juga menunjukkan bahwa lagu-lagu bahasa Inggris sebagai media dapat membantu pronunciation siswa. Hal ini dapat dilihat dari jumlah siswa yang dikategorikan di good to average. Mereka melafalkan vokal dan konsonan hampir benar sepanjang waktu. Singkatnya, lagu bahasa Inggris dapat digunakan untuk mengajarkan pronunciation, terutama untuk siswa kelas sepuluh. Hal ini bahkan digunakan untuk menciptakan suasana yang baik di dalam kelas saat mengajar dan aktivitas belajar berjalan. Kata Kunci: Pelafalan. Lagu bahasa Inggris, siswa kelas X Abstract Pronunciation is one of the important parts in learning English. Pronunciation is needed to accomplish the purpose of oral communication between the speaker and the listener (Hismanoglu, 2006). Therefore, by mastering pronunciation skills the English learner could minimize misunderstanding when they are communicating with other people. However Indonesian students especially in Senior High School still get difficulties in pronouncing the words correctly. It is difficult for Indonesian students to pronounce English word correctly. It is due to the difference between their first language and the target language. The fact above is caused by the way how the teacher teaches the students. Most teachers do not pay attention to the importance of pronunciation. According to harmer (2001:183), teachers feel that they already do a lot of things in teaching pronunciation. Yet, teachers in Indonesia do not know exactly how to teach pronunciation well. They prefer to ask their students to pronounce several words that could make the students bored. As a teacher, they do not only create a good atmosphere during teaching learning activity, but also create a joyful teaching technique. This research is descriptive qualitative research. The instrument used to gain the data of this research is observation checklist and interview. The description of the observation checklist includes: (1) The implementation of English songs to teach pronunciation in the tenth grader of SMA Negeri 4 Surabaya and (2) The students’ pronunciation result during the implementation of English songs in teaching pronunciation. The subject of this research is the students of class X-MIPA7 and the English teacher of SMA Negeri 4 Surabaya. The result of this study showed that the teacher’s implementation of English songs to teach pronunciation ran well. It is showed by the observation result that showed the enthusiasm of the students’ while the teacher gives them songs to learn English.It also showed that English songs as media could assist the students pronunciation. It could be seen from the number of students who were placed in the good to average category. They pronounced the vowel and consonant almost correct all the time. In short, English Songs could be used to teach pronunciation, especially to the students of tenth grade. It could be even used to create a good atmosphere inside the class while teaching and learning activity is running. For the next researcher who will conduct the similar research by using song as a media to teach pronunciation should chose the appropriate song based on the students ability. Keywords: Pronunciation, English songs, Tenth graders